Gambaran Motivasi Belajar Siswa : Sebuah Pendekatan pada Self-Regulated Learning selama COVID-19 - Veronica Kristiyani; Kusumasari Kartika Hima Darmayanti (Indonesian Journal of Behavioral Studies, 2022)
After individuals made an effort to live with COVID-19, the world declared that the disease was now an endemic rather than a pandemic. Numerous things are affected by this, especially education. Students in schools are permitted to participate in instructional and learning activities. However, this modification to the educational system also affected how motivated students were to learn. Therefore, the purpose of this study is to describe the motivation of students to learn. This study used a descriptive quantitative design involving (N = 128). The findings revealed that students' levels of learning motivation fell into two categories, i.e., medium (N = 96.75%) and high (N = 32.25%) with (M = 2.84; SD = 0.276). According to a descriptive analysis, VII students had the highest levels of learning motivation, followed by VIII and IX students; and IX students is with the lowest levels. With regard to self-efficacy, intrinsic values, test anxiety, cognitive strategy utilization, and self-regulation, VII students score best on the subscale. The research findings provide teachers and school psychologists with a foundation for reference as they create educational intervention modules and programs for students in grades VIII and IX to boost their motivation for learning.